Influencing Factors to Stay Off-Campus Living by Students - Sen, Shuvro; Antara, Neel (International Multidisciplinary Research Journal)
The advanced education framework has quickly changed on the planet. In these days, individuals are continually endeavoring to accomplish the higher education. Hence, the demand for the educational institution, leaving spaces, infrastructural development is expanding step by step. This investigation has been embraced to perceive the components that impact an understudy in considering the choice to remain in off-grounds living in the season of advanced education. This investigation has been done through an organized survey & finished by factor analysis strategy. The discoveries demonstrated that maximum understudies pick off-grounds living to guarantee their solace, accommodation, and wellbeing in a peaceful perusing condition. Off-grounds living understudies need to endure enormous challenges regarding cost, transportation, connecting with social activities, and so forth. Government and University experts can take some preventive ways like building lobbies, expanding transportation facilities, diminishing the cost of nourishment, and so forth to minimize the problems of off-grounds livings students.